STUDI PERBANDINGAN HASIL BELAJAR EKONOMI MENGGUNAKAN MODEL PEMBELAJARAN WORLD CAFE DAN ARTIKULASI DENGAN MEMPERHATIKAN MINAT BELAJAR - Muhammad Restu Aji Saputro; Nurdin Nurdin; Tedi Rusman (JEE (Jurnal Edukasi Ekobis), 2019)
This study aims to determine the comparison of economic learning outcomes between World Cafe and Articulated cooperative learning models with regard to student learning interests. The method used in this study is quasi-experimental. The population of this research is Class X students of SMA Negeri 1 Air Naningan in the even semester of the 2018/2019 school year. The population was 144 students with a sample of 72 students. Data collection through observation, interviews, documentation, test techniques and questionnaires. Hypothesis testing uses two-way analysis of variance and two independent sample t-tests. The results showed There was a difference in the average economic learning outcomes of students who learned using the World cafe learning model and students who used the Articulation learning model and There is an interaction between learning models, learning interest in learning outcomes in Economics.Penelitian ini bertujuan untuk mengetahui perbandingan hasil belajar ekonomi antara model pembelajaran kooperatif tipe World Cafe dan Artikulasi dengan memperhatikan minat belajar siswa. Metode yang digunakan dalam penelitian ini adalah eksperimen semu. Populasi penelitian ini adalah siswa Kelas X SMA Negeri 1 Air Naningan semester genap tahun pelajaran 2018/2019. Populasi berjumlah 144 siswa dengan sampel 72 siswa. Pengumpulan data melalui observasi, wawancara, dokumentasi, teknik tes dan angket. Uji hipotesis menggunakan analisis varians dua jalan dan t-test dua sampel independen. Hasil penelitian menunjukkan Ada perbedaan rata-rata hasil belajar Ekonomi pada siswa yang pembelajarannya menggunakan model pembelajaran World cafe dengan siswa yang menggunakan model pembelajaran Artikulasi serta Ada interaksi antara model pembelajaran, minat belajar pada hasil belajar Ekonomi.Kata Kunci: Minat Belajar, Hasil Belajar, World Cafe, Artikulasi